Uniform Signal Redundancy of Parasol and Midget Ganglion Cells in Primate Retina - Gauthier, Jeffrey L. (Society for Neuroscience, 2009)
The collective representation of visual space in high resolution visual pathways was explored by simultaneously measuring the receptive fields of hundreds of ON and OFF midget and parasol ganglion cells in isolated primate retina. As expected, the receptive fields of all four cell types formed regular mosaics uniformly tiling the visual scene. Surprisingly, comparison of all four mosaics revealed that the overlap of neighboring receptive fields was nearly identical, for both the excitatory center and inhibitory surround components of the receptive field. These observations contrast sharply with the large differences in the dendritic overlap between the parasol and midget cell populations, revealing a surprising lack of correspondence between the anatomical and functional architecture in the dominant circuits of the primate retina.